Yule log murder ebook - Meier, Leslie (2018)
Fresh-baked desserts can warm even the frostiest Christmas in coastal Maine. But there's little room for holiday cheer when murder is the new seasonal tradition . . . YULE LOG MURDER by LESLIE MEIER Lucy Stone is thrilled to be cast as an extra in a festive period film—until the set becomes a murder scene. Returning to her role as sleuth, Lucy dashes to restore peace to Tinker's Cove, unwrap a cold-hearted criminal's MO—and reveal how one ornate Yule log cake could possibly cause so much drama. DEATH BY YULE LOG by LEE HOLLIS Hayley Powell's holidays aren't off to a very merry start. Not only has her daughter brought Conner—an infuriatingly perfect new beau—home to Bar Harbor, but a local troublemaker has been found dead with traces of Hayley's signature Yule log cake on his body. . . . And Conner is the prime murder suspect. LOGGED ON by BARBARA ROSS Julia Snowden can't make a decent Bûche de Noël to save her life, so she enlists the help of her eccentric neighbor, Mrs. St. Onge, in hopes of mastering the dessert for Christmas. But with everyone in the older woman's circle missing or deceased, it's up to Julia to stop the deadly tidings before she's the next Busman's Harbor resident to meet a not-so-jolly fate.